New host and geographical records and morphological details for Echinuria skrjabiniensis (Nematoda, Acuariidae) from shorebirds in Argentina - Diaz, Julia Inés (2011)
The acuarioid nematode Echinuria skrjabiniensis Efimov in Skryabin, Sobolev et Ivashkin, 1965 was found in Calidris bairdii and C. fuscicollis (Aves, Scolopacidae) examined from several locations from Patagonia, Argentina. These constitute new host records as well as the first record of this parasite species in South America. Using both light and scanning electron microscopies, new morphological details are provided, including the description of the left spicule and the number and the arrangement of male caudal papillae. The taxonomic history of the species is summarized, corroborating its correct spelling and valid name.